Species‐specific phenological responses to winter temperature and precipitation in a water‐limited ecosystem. Issue 6 (23rd June 2015) - Mazer, Susan J.; Gerst, Katharine L.; Matthews, Elizabeth R.; Evenden, Angela
Abstract : Phenology is the study of seasonal biological events such as flowering, leaf‐out, insect emergence, and animal migration. Long‐term observational studies at numerous temperate zone sites have found that the timing of phenological events responds to temporal variation in climate. To assess the phenological effects of climatic variation on California's flora, The California Phenology Project (CPP) was established in 2010 to develop and to test monitoring protocols and to create tools to support long‐term phenological monitoring and education in several California national parks. The CPP uses standardized protocols developed in collaboration with the USA National Phenology Network (USA‐NPN) to track the phenological status of 30 plant species across key environmental gradients (e.g., latitude, elevation, and precipitation). To date, over 860K phenological records collected by trained citizen scientists, natural resource managers, and park interns participating in the CPP have been contributed to the National Phenology Database. Observations recorded up to twice per week during the first 40 months of monitoring by the CPP were of sufficiently high resolution to detect associations between local climatic conditions and the onset of targeted phenophases. Here, we present analyses of four of the most intensively‐monitored species: Baccharis pilularis (Asteraceae), Quercus lobata (Fagaceae), Sambucus nigra (Caprifoliaceae), and Eriogonum fasciculatum (Polygonaceae). We examined the effects of monthly climate parameters during a four month window (December to March), including mean minimum temperatures (Tmin), total monthly precipitation, and their interactions, on the onset dates of four phenophases per species. Stepwise regressions explained a high proportion (30–99%) of the variation in the onset date of each phenophase. Species and phenophases differed, however, with respect to the strength and the direction of the relationship between each month's conditions (Tmin and/or precipitation) and the timing of vegetative and reproductive phenophases. Given the high climatic variation represented among the monitored sites and among years (2011–2013), it was possible to detect significant associations between local, recent winter conditions and the onset dates of subsequent phenophases, although interactions between monthly conditions were also common. These patterns permit preliminary predictions regarding how these species will respond to future winter warming and intensifying drought.